Throughput and Pricing of Ridesharing Systems - Courcoubetis, Costas; Dimakis, Antonis (Annual Joint Conference of the IEEE Computer and Communications Societies, 2019)
We introduce a queueing model for passengers waiting to get transport by drivers participating in a ridesharing system. The effect of available drivers' mobility pattern, their willingness to accept rides in a given location, and the incentives offered by the platform, on system throughput is considered. We characterize the largest set of passenger arrival rates which can be served by a fixed number of drivers under any policy dictating the mobility pattern of available drivers. It turns out that any rate in this set can be achieved by offering appropriate constant but region-dependent rewards to drivers for passenger pick up. Moreover, it is shown that dynamic rewards which scale in proportion to the number of passengers waiting for pick up in each region, not only maximize throughput but also significantly decrease pick up delays.